2015
DOI: 10.1002/anie.201507626
|View full text |Cite
|
Sign up to set email alerts
|

Nanosized IrOx–Ir Catalyst with Relevant Activity for Anodes of Proton Exchange Membrane Electrolysis Produced by a Cost‐Effective Procedure

Abstract: Abstract:We have developed ah ighly active nanostructured iridium catalyst for anodes of proton exchange membrane (PEM) electrolysis.C lusters of nanosized crystallites are obtained by reducing surfactant-stabilized IrCl 3 in water-free conditions.T he catalyst shows af ive-fold higher activity towards oxygen evolution reaction (OER) than commercial Ir-black. The improved kinetics of the catalyst are reflected in the high performance of the PEM electrolyzer (1 mg Ir cm À2 ), showing an unparalleled low overpot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
132
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 204 publications
(138 citation statements)
references
References 38 publications
6
132
0
Order By: Relevance
“…In ADF-STEM mode, heavy elements such as Ir appear much brighter than the Sn/Sb-containing ATOs upport. [37] Therefore, the interpretation of (S)TEM imaging shouldb eu ndertaken with great care. The result is ah ighly nanostructured compound with S BET = 154 m 2 g À1 .N ote that some bigger spherical Ir/ATO agglomerates could also be observed ( Figure S7).…”
Section: Physicochemical Characterization Of Mw-ir/atomentioning
confidence: 99%
See 1 more Smart Citation
“…In ADF-STEM mode, heavy elements such as Ir appear much brighter than the Sn/Sb-containing ATOs upport. [37] Therefore, the interpretation of (S)TEM imaging shouldb eu ndertaken with great care. The result is ah ighly nanostructured compound with S BET = 154 m 2 g À1 .N ote that some bigger spherical Ir/ATO agglomerates could also be observed ( Figure S7).…”
Section: Physicochemical Characterization Of Mw-ir/atomentioning
confidence: 99%
“…For instance,T seung and Dhara studied Pt supported on ATOv ersus carbon black under harsh conditions in H 3 PO 4 at 150 8C. Amorphous Ir oxide/hydroxides are easily reduced under standard TEM electron-beam conditions, [37] rendering direct observation difficult.A dditionally, chemicali nformation on Ir species is difficult to extract from Xray photoelectrons pectroscopy( XPS) as the debate on lineshape and binding energies of various Ir speciesi ss till ongoing. Similarly,L iu et al reported significant OER activity enhancemento fA TO-supported IrO 2 nanoparticles over bulk IrO 2 owing to higherI rd ispersion and ar esulting higher electrochemically active surfacea rea.…”
Section: Introductionmentioning
confidence: 99%
“…Since no inexpensive and suitable replacement for Ir has been found so far, current research efforts are directed toward a more efficient utilization of Ir based catalysts. 4 Nanoparticulated materials efficiently dispersed on a support, [5][6][7][8] highly porous layers, [9][10][11] core shell 12,13 and mixed oxide systems [14][15][16] have been suggested to reduce the loading of expensive elements. An alternative way is the structural modification of iridium oxides, e.g.…”
mentioning
confidence: 99%
“…Therefore, 5 h tests cannot guarantee that the investigated material is indeed stable. Other authors used chronoamperometry for 0.5 h 34 or chronopotentiometry for 15 h, 6 25 h 36 and 120 h. 5 Instead, investigation of the actual loss of active material directly during polarization can be very helpful to assess the stability on a long run. 37 Such data can be used for estimation of the electrodes end-of-life.…”
mentioning
confidence: 99%
“…The anodic water-splitting reaction, the oxygen evolution reaction (OER), is a significant source of efficiency losses, because it involves multistep proton-coupled electron transfer and sluggish kinetics7. Currently, noble metal-based compounds, such as IrO x and RuO 2 , are the most active OER catalysts, but their scarcity and high cost limit their use in practical applications891011. Therefore, alternative electrode configurations are needed with extraordinary activities and superior long-term stabilities for the OER121314.…”
mentioning
confidence: 99%